2010
DOI: 10.1159/000316640
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor Receptor and HER-2 in Pediatric Embryonal Brain Tumors

Abstract: Background/Aims: Medulloblastomas (MBs), atypical teratoid rhabdoid tumors (AT/RTs) and central nervous system primitive neuroectodermal tumors (PNETs) are aggressive embryonal brain neoplasms in children with overlapping histological features but with different pathogenetic pathways. We set out to evaluate the role of epidermal growth factor receptor (EGFR), HER-2, Ki-67 and p53 in embryonal tumors. Material and Methods: We retrospectively evaluated 36 children with embryonic tumors (27 MBs, 7 AT/RTs and 2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…5b ). Though expression data from MRT and AT/RT tumors and cell lines suggests overexpression of ErbB2/Her2 relative to other central nervous system tumors [ 30 , 31 ], in our system we detect no Smarcb1 dependent change in the expression of ErbB2. ErbB4, as in most cases [ 32 ], is not expressed and unresponsive to Smarcb1 .…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…5b ). Though expression data from MRT and AT/RT tumors and cell lines suggests overexpression of ErbB2/Her2 relative to other central nervous system tumors [ 30 , 31 ], in our system we detect no Smarcb1 dependent change in the expression of ErbB2. ErbB4, as in most cases [ 32 ], is not expressed and unresponsive to Smarcb1 .…”
Section: Resultscontrasting
confidence: 74%
“…6 ). Several studies in human Rhabdoid tumor cells have demonstrated Lapatinib and Gefitinib as highly effective in inhibition of proliferation, consistent with high levels of EGFR / ErbB expression and signaling [ 30 , 45 , 46 ]. Taken together, our results reproduce these findings and reinforce the possibility of targeted EGFR/ErbB therapy in MRT and AT/RT patients.…”
Section: Discussionmentioning
confidence: 94%
“…Nam et al [25] and Meurer et al [26] found a significant correlation of MIB-1 index with patients survival. Likewise, in a previous study we found that a Ki-67 index over 50% was associated with a worse overall survival [27]. …”
Section: Discussionsupporting
confidence: 52%
“…Aberrant growth factor receptor expression and activity has been shown to be important in the pathogenesis of a variety of malignancies, and a variety of growth factors and GFRs are aberrantly expressed in pediatric cancer cells and tumors (Goumnerova 1996;Abella and Park 2009), including the neurotrophin receptors TrkA, TrkB, and TrkC (Thiele et al, 2009); fibroblast growth factor receptors (Janet et al, 1995;Duplan et al, 2002;Goldstein et al, 2007), platelet-derived growth factor receptors (PDGFR) (Matsui et al, 1993;Östman and Heldin, 2007;Thorarinsdottir et al, 2008;Shimada et al, 2008), vascular endothelial growth factor receptors(VEGFR) (Meister et al, 1999;Langer et al, 2000, Fakhari et al, 2002Nowicki et al, 2007;Slongo et al, 2007), c-kit (Shimada et al, 2008;Blom et al, 2010;Puputti et al, 2010), RET (Hishiki et al, 1998), c-Met (Hecht et al, 2004;Li et al, 2005;Diomedi-Camassei et al, 2008), and the ErbB receptor family (EGFR, her-2, her-3, her-4) (Bredel et al, 1999;Bodey et al, 2005;Vasei et al, 2009;Patereli et al, 2010;Izycka-Swieszewska et al, 2011). However, the mechanisms responsible for the regulation of GFR expression in pediatric cancer cells are not well understood.…”
Section: Introductionmentioning
confidence: 99%